Intermolecular interactions and structural organization of a native chitin-chitosan hydrocolloid network resolved by solid-state NMR and molecular dynamics - Qinghui Cheng; Chunyan Lu; Xiufang Gong; Qingyan Wang; Siming Liao; Lihua Chen (Food Hydrocolloids, 2026)

Balancing Ni site supply and interfacial oxygen migration on Ni–Fe–CeO2 catalysts for coke resistant dry reforming of methane - Xuanyu Ji; Yuqin Cheng; Qiufan Qu; Qinghui Yu; Xiong Zhou; Yu Yang; Wenli Song; Haoran Wang; Lu Yang (Fuel, 2026)

Dynamic changes in flavor characteristics of marinated silver carp during marinating: Insight from amino acid metabolic pathways - Shi Nie; Lu Zhang; Jingtao Hu; Ruixi Liu; Qinghui Wen; Qiao Ding; Chunming Tan; Zongcai Tu (Food Research International, 2025)

A Study on Energy Loss and Transient Flow Characteristics of a Large Volute Centrifugal Pump During Power-Off Process Under Cavitation Conditions - Qingzhao Pang; Desheng Zhang; Gang Yang; Xi Shen; Qiang Pan; Linlin Geng; Qinghui Lu (Journal of Marine Science and Engineering, 2025)
A novel pumped storage system using centrifugal pumps to transfer water between reservoirs in coastal hydropower plants has significantly mitigated grid instability. However, frequent start–stop operations of large vertical centrifugal pumps, which serve as the core equipment, severely affect the operational stability of these systems. In this study, the intrinsic connection between the cavitating flow field and irreversible losses during the process was analyzed using the entropy production theory. The time–frequency characteristics of pressure pulsation in pump were analyzed by using the continuous wavelet transform. The results indicate that with the reduction in the flow rate and rotational speed, the sheet cavitation at the impeller inlet rapidly weakens until it vanishes. The cavity cavitation within the draft tube commences to emerge in the turbine mode. Separation vortices are formed due to the mismatch in the flow angle at the impeller outlet. These vortices induce local cavitation, causing both a rapid energy loss increase and high-amplitude, low-frequency pressure pulsations. During transient processes, flow instabilities induce high-amplitude, low-frequency pressure pulsations within the stay vane region, with maximum amplitude attained during runaway condition. The research results provide a theoretical foundation for the stable operation of centrifugal pumps.

Proposal for ecological operation of cascade reservoirs to safeguard reproductive migration and egg development in drifting-egg fish - Xiaoyao Yan; Zefan Yang; Qinghui Zeng; Qin Yang; Qianheng Lu; Long Yan; Huan Liu; Peng Hu (Journal of Cleaner Production, 2025)

Increased Nitrogen Application Alleviates Straighthead Disease by Reducing Dimethylarsinic Acid Accumulation and Promoting Mineral Nutrient Uptake in Rice - Qinghui Liu; Cuihua Bai; Weisheng Lu; Zhijun Zhang; Xueying Yin; Wanting Lin; Lixian Yao (Journal of Soil Science and Plant Nutrition, 2025)

Local contributions and climate change effects on organochlorine pesticide levels in soil and sediments in Svalbard - Yan Lin; Geir Wing Gabrielsen; Zhibo Lu; Qinghui Huang; Peng Huang; Hongwei ke; Minggang Cai (Environmental Pollution, 2025)

Effects of piperine on the growth performance, digestive enzyme activity, lipid metabolism, and antioxidant capacity of juvenile large yellow croaker (Larimichthys crocea) fed with high soybean oil diet - Shijie Pan; Yongtao Liu; Zhen Wang; Xianyong Bu; Wencong Zhang; Wenchang He; Jinze Zhang; Chuanwei Yao; Yuhang Tang; Zengqi Zhao; Lu Zhang; Kangsen Mai; et al. (Aquaculture, 2024)

Fracture stratigraphy in oil-rich shale of the Upper Xiaganchaigou Formation (upper Eocene), western Qaidam Basin - Rui Liu; Shuanglong Shi; Kunyu Wu; John N. Hooker; Guoyong Liu; Songtao Wu; Qinghui Zhang; Lu Xu; Guoxin Li; Xiucheng Tan (Marine and Petroleum Geology, 2024)

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Determination of organotin compounds in marine sediments from Arctic Svalbard and West Antarctic Fildes Peninsula - Chunzhao Chen; Ling Chen; Qinghui Huang; Gang Yu; Zhibo Lu; Geir Wing Gabrielsen (Marine Pollution Bulletin, 2024)

Driving forces and recovery potential of the macrophyte decline in East Taihu Lake - Changtao Yang; Xiaobing Shen; Jianbin Wu; Xinyi Shi; Zhijie Cui; Yuwei Tao; Haiming Lu; Jianhua Li; Qinghui Huang (Journal of Environmental Management, 2023)

Cadmium, arsenic, and mineral nutrients in rice and potential risks for human health in South China - Qinghui Liu; Weisheng Lu; Cuihua Bai; Congzhuo Xu; Maozhi Ye; Yongcong Zhu; Lixian Yao (Environmental Science and Pollution Research, 2023)

Distribution, driving forces, and risk assessment of 2-MIB and its producer in a drinking water source-oriented shallow lake - Xinyi Shi; Qinghui Huang; Xiaobing Shen; Jianbin Wu; Jing Nan; Jianhua Li; Haiming Lu; Changtao Yang (Environmental Science and Pollution Research, 2023)

Effects of different dietary lipid sources on growth performance, hepatic lipid deposition and transcriptome response in spotted sea bass (Lateolabrax maculatus) - Guoxiong Jin; Lu Zhang; Kangsen Mai; Xiaoru Chen; Shude Xu; Qinghui Ai (Aquaculture, 2023)

Effects of supplemental glycerol monolaurate on growth, hepatic lipid metabolism, antioxidant capacity and mitochondrial function of large yellow croaker (Larimichthys crocea) fed diets with high soybean oil level - Yuhang Tang; Zhou Zhang; Lu Zhang; Yuliang He; Ning Xu; Wei Fang; Tingting Hao; Kangsen Mai; Qinghui Ai (Aquaculture, 2023)

Impact of submerged macrophytes on growth and 2-MIB release risk of Pseudanabaena sp.: From field monitoringa to cultural experiments - Changtao Yang; Xiaobing Shen; Xinyi Shi; Zhijie Cui; Jing Nan; Haiming Lu; Jianhua Li; Qinghui Huang (Journal of Hazardous Materials, 2023)

Simulation of Seismic Dynamic Response and Post-failure Behavior of Jointed Rock Slope Using Explicit Numerical Manifold Method - Zuyang Ye; Jiahai Xie; Ruili Lu; Wei Wei; Qinghui Jiang (Rock Mechanics and Rock Engineering, 2022)

Identification of the TF-miRNA-mRNA co-regulatory networks involved in sepsis - Xiaoqian Luo; Weina Lu; Jianfeng Zhao; Jun Hu; Enjiang Chen; Shi Fu; Qinghui Fu (Functional & Integrative Genomics, 2022)

Investigation of microplastic pollution in Arctic fjord water: a case study of Rijpfjorden, Northern Svalbard - Mengrong Bao; Qinghui Huang; Zhibo Lu; France Collard; Minggang Cai; Peng Huang; Yong Yu; Shuiping Cheng; Lihui An; Anette Wold; Geir Wing Gabrielsen (Environmental Science and Pollution Research, 2022)

Indoor formaldehyde removal by three species of Chlorphytum Comosum under the long-term dynamic fumigation system - Jian Li; Jiaochan Zhong; Ting Zhan; Qinghui Liu; Liushui Yan; Mingming Lu (Environmental Science and Pollution Research, 2019)

Expression analysis of argonaute, Dicer-like, and RNA-dependent RNA polymerase genes in cucumber (Cucumis sativus L.) in response to abiotic stress - DEFANG GAN; MENGDAN ZHAN; FENG YANG; QIQI ZHANG; KELING HU; WENJUAN XU; QINGHUI LU; LING ZHANG; DANDI LIANG (Journal of Genetics, 2017)

Heavy metals in aquatic organisms of different trophic levels and their potential human health risk in Bohai Bay, China - Yan Zhang; Xueqiang Lu; Naili Wang; Meinan Xin; Shiwei Geng; Jing Jia; Qinghui Meng (Environmental Science and Pollution Research, 2016)

A Study on the Vibration Frequency of Blasting Excavation in Highly Stressed Rock Masses - Jianhua Yang; Wenbo Lu; Qinghui Jiang; Chi Yao; Shuihua Jiang; Lin Tian (Rock Mechanics and Rock Engineering, 2016)

Diethylstilbestrol in fish tissue determined through subcritical fluid extraction and with GC-MS - Qinghui Qiao; Nianrong Shi; Xiaomei Feng; Jie Lu; Yuqian Han; Changhu Xue (Journal of Ocean University of China, 2016)

Effect of dietary olaquindox on the growth of large yellow croaker (Pseudosciaena crocea R.) and the distribution of its residues in fish tissues - Huitao Li; Weifang Wang; Kangsen Mai; Qinghui Ai; Chunxiao Zhang; Lu Zhang (Journal of Ocean University of China, 2014)

Replacement of dietary fish oil with vegetable oils improves the growth and flesh quality of large yellow croaker (Larmichthys crocea) - Qingyuan Duan; Kangsen Mai; Jikang Shentu; Qinghui Ai; Huiying Zhong; Yujian Jiang; Lu Zhang; Chunxiao Zhang; Sitong Guo (Journal of Ocean University of China, 2014)

Isolation and characterization of twelve novel polymorphic microsatellite loci in the Branchiostoma belcheri Gray (Amphioxus) - Gang Dai; Yuanyue Li; Zhongbao Li; Qinghui Li; Yuanyu Cao; Jingbo Shangguan; Yefeng Ning; Huan Yang; Jing Lu (Conservation Genetics Resources, 2013)

Effects of dietary menhaden oil, soybean oil and soybean lecithin oil at different ratios on growth, body composition and blood chemistry of juvenile Litopenaeus vannamei - Yi Hu; Beiping Tan; Kangsen Mai; Qinghui Ai; Lu Zhang; Shixuan Zheng (Aquaculture International, 2011)